Realising the Rural Telephony Project - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Realising the Rural Telephony Project, Vanguard (Lagos), November 2002 For most Nigerians, the most significant achievement of the Obasanjo administration is the successful implementation of GSM telephony in Nigeria.